The Relationship between Work Posture and Nutritional Status with Complaints of Musculoskeletal Disorders in the Driver - Ramadan, Novrizal; Suraya, Rani; Aidha, Zuhrina (Indonesian Journal of Global Health Research, 2024)
Work posture is a reference to the position of the body when carrying out activities in a job, the driver profession really needs more attention to this. Good work posture is able to adjust the sitting or standing position to be ergonomic, keep the back straight, and avoid tension in certain parts. This study aims to determine the relationship between work portur and nutritional status with complaints of musculoskeletal disorders in trans metro deli medan drivers. This research method uses Cross-sectional study. The study runs from February to March in 2024. Located at Trans Metro Deli Medan Bus Stop corridors 1 to 5. Populasai in this study amounted to 151 drivers using stratified random sampling techniques. The determination of the number of samples in this study used the table determining the number of samples of Issac &Michael which obtained a sample of 105 samples with an error rate of 5%. The results of statistical analysis using the chi square test Based on the results of bivariate analysis of work posture has a relationship with complaints of musculoskeletal disorders (p = 0.034), as well as nutritional status can be concluded to have a relationship with complaints of musculoskeletal disorders (p = 0.048), so it can be known that there is a significant relationship between nutritional status and complaints of musculoskeletal disorders On Trans Metro Deli Medan driver. The relationship between work posture and nutritional status with complaints of musculoskeletal disorders in trans metro deli medan drivers, each driver is expected to stretch and rest enough to avoid work fatigue and musculoskeletal disorders, trans metro deli medan drivers are also expected to maintain body mass index in normal nutritional status.